Depressive Symptoms Partially Mediate the Association of Frailty Phenotype Symptoms and Cognition for Females but Not Males. (January 2023) - Resciniti, Nicholas V.; Farina, Mateo P.; Merchant, Anwar T.; Lohman, Matthew C.
Objectives: We aimed to evaluate whether depressive symptoms mediated the relationship between frailty phenotype and cognitive function by sex. Methods: Data came from the Health and Retirement Study from 2012–2016. The outcome was measured by Fried's frailty criteria, our outcome was continuous global cognition, and mediator was depressive symptoms. We used mediation analysis, stratified by sex, to estimate the direct and indirect effects of frailty symptoms on cognition mediated by depressive symptoms. Results: Males had a larger total effect (β= −0.43; 95% CI: −0.66, −0.02) for lower cognitive score for each increase in frailty symptom compared to females (β= −0.28; 95% CI: −0.47, −0.08). A significant indirect effect from frailty phenotype to cognition was found through depressive symptoms for females but not males. Conclusion: These results highlight the importance of identifying individuals with frailty and depressive symptoms to monitor and provide interventions to preserve cognitive function.